2020
DOI: 10.1109/access.2020.3038676
|View full text |Cite
|
Sign up to set email alerts
|

Active Learning Based Federated Learning for Waste and Natural Disaster Image Classification

Abstract: The feasibility of Federated Learning (FL) is highly dependent on the training and inference capabilities of local models, which are subject to the availability of meaningful and annotated data. The availability of such data is in turn contingent on the tedious and time-consuming annotation job that typically requires the manual analysis of training samples. Active Learning (AL) provides an alternative solution allowing a Machine Learning (ML) model to automatically choose and label the data from which it lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 35 publications
(45 reference statements)
0
35
0
Order By: Relevance
“…Since federated learning is an emerging field, its use in handling noise data is rarely covered. So this article refers to Ahmed et al (2020) , Ye et al (2020) , Li, Wang & Guan (2019) , Xu et al (2022) , Seth, Swain & Mishra (2018) , Zhang et al (2018) for a comparative analysis of federated learning algorithms applied to different domains with the mechanism proposed in this article, as shown in Table 1 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since federated learning is an emerging field, its use in handling noise data is rarely covered. So this article refers to Ahmed et al (2020) , Ye et al (2020) , Li, Wang & Guan (2019) , Xu et al (2022) , Seth, Swain & Mishra (2018) , Zhang et al (2018) for a comparative analysis of federated learning algorithms applied to different domains with the mechanism proposed in this article, as shown in Table 1 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The scheme in [8] also considered FL based single-task disaster classification, with additional concern regarding the annotation burden for each local training. Armed with AL, the authors reported that the proposed AL-based FL framework performs equally well under two strategies namely uncertainty sampling and query by committee.…”
Section: Federated Learning (Fl) and Active Learning (Al)mentioning
confidence: 99%
“…A few recent works such as [8][9] have demonstrated the promising performance of disaster classification via FL. However, training-level evaluation results do not necessarily translate into good inference performance.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the classification model trained on an actively selected subset of annotated instances reaches in average a superior performance to a model trained on a randomly selected subset. AL strategies have been successfully employed in several applications, e.g., malware detection [21], waste classification [22], classification of medical images [23], and training of robots [24]. However, many of these AL strategies make three central assumptions that limit their practical use [25], and we refer to them as traditional AL.…”
Section: Introductionmentioning
confidence: 99%